Venkovský cestovní ruch Aktuální témata cestovního ruchu - Šíp, Jiří (Masaryk University Press, 2020)
Title in English: Rural Tourism: Current Topics in Tourism. The book Rural Tourism is collective work of a team of members of the Association SVECR. After the monograph Municipal Tourism (2017), it is the second book from a series entitled Current Topics in Tourism. This monograph aims to present a wide range of issues related to rural tourism, which can be considered a possible option for establishing sustainable development in rural areas. The need for regular maintenance of the cultural landscape of the countryside requires the development of new alternative programs which will include tourism as one component. The publication includes the new insights contributing to the formation of a theoretical foundation, research projects and key studies about rural tourism in the Czech Republic. It presents possible options and current topics for next research in this area.